The Influences of Compensation and Supply Chain Managemnet towards Educatioan System: The Mediating Role of Job Motivation - Faisal Matriadi; Siti Raha Agoes Salim; Ritha F.Dalimunthe; Parapat Gultom (International Journal of Supply Chain Management, 2019)
The education service today's is increasingly competitive and supply chain management in this system can be distinguish. It is encouraging schools at this time to improve their performance. One way can be used to improve teacher performance is job motivation. Therefore, the purpose of this study was to analyze the role of job motivation as mediating variable in the relationship between compensation and competence towards teacher performance in Lhokseumawe. A total of 351 teachers from seven senior high schools were participated and collected using cluster random sampling. There are seven hypotheses were formulated as well as for direct and indirect effects (mediating) and performed by using statistical software namely WarpPLS 3.0. The results show that compensation and competence have a significant relationship on job motivation. Also, the result indicate that the compensation, competence and job motivation have a significant relationship on teacher performance. In addition, job motivation has mediated the relationship between compensation and competence towards teacher performance among senior high school teacher in Lhokseumawe.